2014
DOI: 10.2147/jpr.s63028
|View full text |Cite
|
Sign up to set email alerts
|

An open-label, long-term study examining the safety and tolerability of pregabalin in Japanese patients with central neuropathic pain

Abstract: PurposeStudies of pregabalin for the treatment of central neuropathic pain have been limited to double-blind trials of 4–17 weeks in duration. The purpose of this study was to assess the long-term safety and tolerability of pregabalin in Japanese patients with central neuropathic pain. The efficacy of pregabalin was also assessed as a secondary measure.Patients and methodsThis was a 53-week, multicenter, open-label trial of pregabalin (150–600 mg/day) in Japanese patients with central neuropathic pain due to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 22 publications
8
30
0
2
Order By: Relevance
“…In order to make data from the current dry eye sample comparable to these studies, only subjects who rated their average eye pain during the past week as at least 4 out of 10 on a NRS were included, as this was equivalent to the inclusion criteria for the previously published studies that were used for comparison. 32-35 Our patient cohort fell in the mid-range of scores compared to the other data taken from the literature, and appears most similar to the central neuropathic pain patients studied by Onouchi et al 33 …”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…In order to make data from the current dry eye sample comparable to these studies, only subjects who rated their average eye pain during the past week as at least 4 out of 10 on a NRS were included, as this was equivalent to the inclusion criteria for the previously published studies that were used for comparison. 32-35 Our patient cohort fell in the mid-range of scores compared to the other data taken from the literature, and appears most similar to the central neuropathic pain patients studied by Onouchi et al 33 …”
Section: Resultssupporting
confidence: 67%
“… SF-MPQ=short-form McGill Pain Questionnaire; SD=standard deviation. Siddall et al study 32 included patients with central neuropathic pain conditions from spinal cord injury. Onouchi et al study 33 included patients with central neuropathic pain conditions from spinal cord injury (37%), cerebral stroke (58%), and multiple sclerosis (5%). * In order to make data from the current dry eye sample comparable to those from the literature, only subjects who rated their average eye pain during the past week at least 4 out of 10 on a NRS were included. † P value comparison of means between non-ocular pain population and dry eye population <0.05 (2 tailed independent t test). …”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…The findings demonstrated that PGB is generally well-tolerated and provides a sustained efficacy over 53-week treatment period in patients with chronic central neuropathic pain. 8 A randomized double-blind placebo (PL) controlled study was done by Mishra et al, in 2012 to evaluate the comparative clinical efficacy of amitriptyline, gabapentin, and PGB in neuropathic cancer pain. A total of 120 patients were enrolled in the study and divided into four groups.…”
Section: Review Of Earlier Studies For Efficacy and Tolerabilitymentioning
confidence: 99%
“…However, the use of pregabalin for CPSP still requires further research. 10 Pregabalin in the United States is registered for diabetic neuropathy pain therapy, spinal cord injury, post-herpetic neuralgia, and adjunctive therapy for adult partial seizure. In Europe, pregabalin is indicated for the treatment of central and peripheral neuropathic pain, epilepsy, and generalized anxiety disorder.…”
Section: Introductionmentioning
confidence: 99%